2012
DOI: 10.1037/a0025948
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being and adaptation to life events: A meta-analysis.

Abstract: Previous research has shown that major life events can have short- and long-term effects on subjective well-being (SWB). The present meta-analysis examines (a) whether life events have different effects on cognitive and affective well-being and (b) how the rate of adaptation varies across different life events. Longitudinal data from 188 publications (313 samples, N = 65,911) were integrated to describe the reaction and adaptation to four family events (marriage, divorce, bereavement, child birth) and four wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

77
937
10
41

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,102 publications
(1,065 citation statements)
references
References 261 publications
(134 reference statements)
77
937
10
41
Order By: Relevance
“…Furthermore, the base of the beam balance can change its height to account for long-term shifts in well-being, allowing for homeostasis at a new level. A recent meta-analysis of longitudinal studies of adaption to various life events and the effects on affective and cognitive SWB [32] challenged the notion of life events having no lasting effect on well-being, which is mainly supported by cross-sectional studies. Analysing the effect and adaptation curve of affective and cognitive SWB as well as eight life events separately, they found that life events affect both types of SWB differentially in terms of both the initial hedonic reaction and the rate of adaption, whereby most events initially and persistently affected cognitive SWB more negatively than affective SWB.…”
Section: Self-acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the base of the beam balance can change its height to account for long-term shifts in well-being, allowing for homeostasis at a new level. A recent meta-analysis of longitudinal studies of adaption to various life events and the effects on affective and cognitive SWB [32] challenged the notion of life events having no lasting effect on well-being, which is mainly supported by cross-sectional studies. Analysing the effect and adaptation curve of affective and cognitive SWB as well as eight life events separately, they found that life events affect both types of SWB differentially in terms of both the initial hedonic reaction and the rate of adaption, whereby most events initially and persistently affected cognitive SWB more negatively than affective SWB.…”
Section: Self-acceptancementioning
confidence: 99%
“…Similar to the concept of resilience, no consensus on the definition or measurement of well-being has been reached so far [13,15,16,[30][31][32][33]. For example, while the WHO has defined well-being as the 'presence of positive mental health' 6 [9, p. 10], others have equated it to 'happiness' (e.g., [30]).…”
Section: Well-beingmentioning
confidence: 99%
“…Research has shown that unemployed people typically experience a sharp decline in subjective well-being after job loss, followed by a gradual adaptation period (Luhmann et al 2012). Adaptation to long-term unemployment, however, may be slow and remain incomplete (Clark et al 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Der Übergang in den Ruhestand gilt zunächst als neutrales Ereignis, als Entwicklungsaufgabe, die im Lebenslauf verankert ist. Der Übergang kann sich jedoch zum kritischen Lebensereignis entwickeln (Barbosa et al 2016;Hübner 2016;Luhmann et al 2012). Kritische Lebensereignisse können als anregend und zugleich belastend empfunden werden, z.…”
Section: Der Ruhestandsprozess Als Herausforderungunclassified
“…Insgesamt kommen bisherige empirische Studien also zu dem Ergebnis, dass der Verlauf der Anpassung an den Ruhestand bei der Mehrzahl der befragten Personen über die Zeit hinweg tendenziell positiv ist (Luhmann et al 2012;Pinquart und Schindler 2007;Wang 2007 …”
Section: Diskussion Und Schlussfolgerungenunclassified